Polystoma floridana n. sp. (Monogenea: Polystomatidae) a parasite in the green tree frog, Hyla cinerea (Schneider), of North America - du Preez, Louis H.; Verneau, Olivier; Gross, Timothy S. (Zootaxa, 2007)
Polystoma floridana is described as a new species of the Polystomatidae parasitic in the urinary bladder of Hyla cinerea in Gainesville, Florida, USA. This is the fifth polystome from an anuran host described from North America but only the third belonging to the genus Polystoma. Here we show that the parasite from H. cinerea is a separate species. It is distinguished from other American Polystoma species by a combination of characters including body size, haptor length, body rations, size and shape of hamuli and marginal hooklets. In a sample of 235 frogs, 13.6% were infected with up to four parasites per host (mean intensity 1.6).